The importance of educational activities promoting health in obstetrics and gynaecology-selected issues taking into account nutritional aspects - Katarzyna Plagens-Rotman; Piotr Merks; Grażyna Jarząbek-Bielecka; Witold Kędzia; Marika Kujawa; Aneta Bax-Adamowicz; Małgorzata Mizgier (IMR Press, 2021)
Objective: It is important in the context of gynaecology and obstetrics that the risk of many diseases can be significantly reduced by introducing a number of lifestyle changes, such as diet. Mechanism: An unhygienic lifestyle with an unbalanced diet, eating food of inadequate health quality, can have a significant negative impact on a woman's health. Findings in brief: It is essential to continue research on the influence of environmental and genetic factors on health, which is important in the context of gynaecology and obstetrics where any educational activities promoting women's health matter. Conclusions: Educational activities promoting a hygienic lifestyle and a proper diet play a huge role in protecting women's health.